2018
DOI: 10.1016/j.jfoodeng.2018.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure carbon dioxide on tomato juice: Inactivation kinetics of pectin methylesterase and polygalacturonase and determination of other quality parameters

Abstract: Tomato juice, Lycopersicon esculentem cv. Canario, has been treated by HPCD as non-thermal preservation treatment. The inactivation kinetics for pectinmethylesterase (PME) and polygalacturonase (PG) were determined at different pressures (8.5 to 20 MPa) and temperatures (35 to 55 ºC). At the highest operating pressure and temperature essayed in this work, it was found that PME could be almost completely inactivated, whereas PG resulted to be more HPCD resistant at the working conditions. PME enzyme inactivatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The increase in viscosity after HPCD treatment might also be related to the decrease of particle size. Effect of HPCD on particle size distribution has been reported in previous publications (Briongos et al, 2016;Illera et al, 2018). It demonstrated that HPCD led to homogenization effect causing smaller particles of juice colloid.…”
Section: Apparent Viscositymentioning
confidence: 62%
See 2 more Smart Citations
“…The increase in viscosity after HPCD treatment might also be related to the decrease of particle size. Effect of HPCD on particle size distribution has been reported in previous publications (Briongos et al, 2016;Illera et al, 2018). It demonstrated that HPCD led to homogenization effect causing smaller particles of juice colloid.…”
Section: Apparent Viscositymentioning
confidence: 62%
“…Hence, the viscosity would increase. Moreover, the homogenization effect caused by HPCD could also promote the release of soluble materials such as pectin from the particles, then increase the viscosity (Illera et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The juiciness of the tomato fruit is a very important internal attribute for the end consumer (Oltman et al, 2014). The increase in the juiciness of fruits is due to the activity of the enzyme polygalacturonase, which produces low-molecular weight pectins (Illera et al, 2018). Juiciness also depends on the activity of the enzyme pectin methylesterase, which inhibits polygalacturonase and produces high-molecular weight pectins that congeal in water (Wormit and Usadel, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, Illera et al . (2018) on a selective inactivation of PME found polygalacturonase (PG) in tomato juice with HPP eliciting a homogenisation effect of tomato juice, where the overall particle size distribution was attenuated.…”
Section: Control Of Mycotoxinsmentioning
confidence: 99%